Reaktioner på triggers och hägnutnyttjande hos dholen (Cuon alpinus) - Krafft, Sanna (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
The dhole (Cuon alpinus) is a highly social species that lives in groups and communicates through a broad repertoire of sounds both in captivity and in the wild. The dhole is classified as endangered since 2004 by the IUCN red list. Animals in captivity always experience some sort of behaviour limitations due to containment and limited space which can affect animal welfare. Enclosure design is therefore of great importance to meet the behavioral needs of the specific species and provide adequate welfare. Behavioral studies and space utilization studies are two good methods to investigate animal welfare in captive animals. To investigate behaviour and space utilization of dholes, behaviour observations of seven group held dholes were carried out in Eskilstuna Parken Zoo during the 3rd to 16th of April. Vocalization and other behaviors in relation to triggers were recorded and space utilization were also recorded. A comparison of space utilization between this study and a previous study was made. The results from the behaviour study show that the behaviour low vocalization was the behaviour performed the most and occurred the most in relation to nothing outside. The behaviour unaffected was the behaviour shown the most in relation to triggers and in relation to performed behaviour. The behaviour observant was performed towards most triggers and most often towards the staff´s, which handled the predators, car but also the staff. The behaviour low vocalization was also performed towards the staff´s car and the staff. The behaviour eating was performed the least both in relation in performed behaviour and in relation to triggers. So the dholes do show interest in their environment and they vocalize the most when there is nothing outside their enclosure but also in relation to some triggers such as the staff´s car and the staff members as well and they are a very observant species that shows attention to most of the triggers. The results from the space utilization study show that the dholes spent most time unseen followed by zone 12 that was close by the enclosures perimeter and visitors as well as staff members. Zone 10 was used the least and contained an empty pound. All zones in the enclosure were used, but to varying degree. There had also been a shift in utilization from the previous study. So the dholes do utilize the whole enclosure but some zones more than others and there is a difference in space utilization compared to the previous study, which can indicate welfare since it might be a sign of the absence of stereotypic behaviors.